Cloning and characterization of a phosphomevalonate kinase gene that is involved in saponin biosynthesis in the sea cucumber Apostichopus japonicus. Issue 128 (September 2022) - Jiang, Pingzhe; Gao, Shan; Chen, Zhong; Sun, Hongjuan; Li, Peipei; Yue, Dongmei; Pan, Yongjia; Wang, Xuda; Mi, Rui; Dong, Ying; Jiang, Jingwei; Zhou, Zunchun
Abstract: The sea cucumber Apostichopus japonicus is one of the most dominant and economically important aquaculture species in China. Saponin, which possesses notable biological and pharmacological properties, is a key determinant of the nutritional and health value of A. japonicus . In the present study, we amplified the full-length cDNA of a phosphomevalonate kinase (PMK) gene (named AjPMK) using rapid amplification of cDNA ends (RACE). Subsequently, we engineered a recombinant AjPMK (rAjPMK) protein and assessed its enzymatic activity by enzyme-linked immunosorbent assay (ELISA). Proteins that interact with rAjPMK were screened and identified via pull-down assay combined with liquid chromatography with tandem mass spectrometry (LC-MS/MS). We found that the full-length cDNA of AjPMK contained 1354 bp and an open reading frame (ORF) of 612 bp. The AjPMK protein was predicted not to contain a signal peptide but to contain a phosphonolate kinase domain seen in higher eukaryotes and a P-loop with a relatively conserved nucleoside triphosphate hydrolase domain. The molecular weight of the AjPMK protein was estimated to be 23.81 kDa, and its isoelectric point was predicted to be 8.72. Phylogenetic analysis showed that AjPMK had a closer evolutionary relationship with genes from starfish than with those of other selected species. Besides, we found that rAjPMK synthesized mevalonate-5-diphosphate, interacted either directly or indirectly with crucial pattern recognition receptors (PRRs) and was regulated by immune-related processes, including antioxidative reactions, stress resistance responses and enzyme hydrolysis. Moreover, AjPMK also interacted with farnesyl pyrophosphate synthase, an enzyme reported to be involved in saponin biosynthesis. Together, our findings implied that AjPMK may be directly involved in saponin biosynthesis and the regulation of various innate immune processes. Highlights: A phosphomevalonate kinase (PMK) gene was identified in sea cucumber Apostichopus japonicus . AjPMK is involved in sea cucumber saponin biosynthesis. AjPMK might be regulated by multiple immune processes.